Pengaruh Gaya Kepemimpinan Dan Motivasi Terhadap Kinerja Karyawan Pt. Iss Indonesia Area Pt. KievitIndonesia Di Salatiga - Hasanah, Mafidatun, Ma'ruf, Drs., M.M (2017)
This study aim to determine the effect of leadership style and motivation on employee performance PT. ISS Indonesia are PT. Kievit Indonesia in Salatiga.This research is a uantitative research. The over all population to be sampled inthe study. Extracting information to the 55 employees who were the respondentsin the study, carried out using a questionnaire organized into five Likert scale.Data analysis methods used are validity, reliability test, and test multiple linearregression analysis with t-test, F, and the coefficient of determination (R²).Hypothesis tests showed the influence of leadership style and motivation have significant influence with t respectively 4.616 and 3.407. In the F test showed thattogether the variables of leadership style and motivation have a significant effect on the performance of employees with a probability value of 0.000 (0.000 <0.05).And the coefficient of determination (R ²) amounted to 56.67%.